2013
DOI: 10.5505/jkartaltr.2013.92300
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sociodemographic factors of children with enuresis

Abstract: Amaç: Bu çalışmada Çocuk Polikliniği'ne başvuran çocuklarda enürezisle ilişkili sosyodemografik faktörlerin değerlendirilmesi amaçlandı. Gereç ve Yöntem: Enürezisli çocukların (n=131) aileleri ile yapılan görüşmelerden elde edilen veriler değerlendirildi. Olgular cinsiyet, başvuru yaşları, ailede enürezis öyküsü, eşlik eden hastalık, uyku derinliği ve tedavi yöntemi ile sosyoekonomik açıdan ailenin gelir düzeyine göre incelendi. Bulgular: Olguların 86'sı (%65.6) erkek, 45'i (%34.4) kızdı. Başvuru yaşı açısında… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It was determined in our study that the frequency of urinary incontinence was more common in boys, but this difference was not significant. Ozgurhan et al 24 also found a higher rate of urinary incontinence in boys. Similarly, in another study, 25 it was found that urinary incontinence was at a higher level in boys, but the difference was not significant.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It was determined in our study that the frequency of urinary incontinence was more common in boys, but this difference was not significant. Ozgurhan et al 24 also found a higher rate of urinary incontinence in boys. Similarly, in another study, 25 it was found that urinary incontinence was at a higher level in boys, but the difference was not significant.…”
Section: Discussionmentioning
confidence: 89%
“…We determined that 120 (56%) of the children with urinary incontinence had not been taken to any health facility previously due to this problem. It has been stated in the literature 24,55,56 that parents do not seek treatment because of a history of urinary incontinence in the family, believing that the condition would disappear spontaneously, and for fear that prescribed drugs could cause infertility.…”
Section: Ta B L Ementioning
confidence: 99%
“…In our study, it was found that 56% of the children with urinary incontinence problem had not been taken to any health institution before due to this problem. In the literature (42)(43)(44), it was stated that families also did not seek treatment because they had a history of urinary incontinence, believed that it would recover spontaneously, and fear that the drugs used could cause infertility. This result showed the importance of detecting children with urinary incontinence problems by screening and the need for medical information for the families of children with problems.…”
Section: Discussionmentioning
confidence: 99%